Polymorphism of gene Hemagglutinin and its influence on the properties of influenza virus a H1N1 and H7N9 strains - Buriachenko, Semen; Stegniy, Borys (ScienceRise: Biological Science, 2019)
Influenza virus A is a causative agent of zoonotic and anthroponosis diseases. Virulence and contagious properties of the influenza virus are dependent on the presence of hemagglutinin. The membrane glycoprotein hemagglutinin has an important part in the adhesion and invasion of the influenza virus to the cell, as well as in the formation of immunity of the host organism. Hemagglutinin forms pandemic properties of influenza strains. Systematics and characterization of the influenza virus strains are based in particular on the type of hemagglutinin. The most contagious strains of the influenza A virus are strains H1N1 and H7N9. Polymorphism of hemagglutinin and its effect on the properties of influenza strains makes it relevant to study its variability. The aim of the study. The purpose of the study was to determine the polymorphism of the hemagglutinin encoding gene of strains of the influenza A H1N1 and H7N9 strains, to determine its effect on the polymorphism of the amino acid sequences of hemagglutinin and the properties of the strains by bioinformatic research methods. Materials and methods. The nucleotide sequences of hemagglutinin of influenza A H1N1 and H7N9 strains and products of its translation were analyzed by cluster analysis. The properties of hemagglutinin were defined by determining its domains. Results and discussion. As a result of the study, the polymorphism and genetic distances between the alleles of the gene encoding hemagglutinin of the influenza virus have been calculated and its translation has been carried out. The polymorphism and amino acid distances between the products of its translation were detected; a comparative analysis between the nucleotide and amino acid sequences was performed. The influence and effect of synonymouscodons in the nucleotide sequences of the alleles of the hemagglutinin encoding gene on the hemagglutinin polymorphism was shown. The domains of the test samples of hemagglutinin were identified. Conclusions. As a result of studies, the absence of the influence of the polymorphism of the hemagglutinin encoding gene on the hemagglutinin polymorphism was shown. The absence of the effect of polymorphism on the amino acid sequences of hemagglutinin of influenza A H1N1 and H7N9 strains, as well as on the domain composition and, thus, on the properties of strains was determined